2019
DOI: 10.1038/s41467-019-12413-0
|View full text |Cite
|
Sign up to set email alerts
|

A fiber-deprived diet disturbs the fine-scale spatial architecture of the murine colon microbiome

Abstract: Compartmentalization of the gut microbiota is thought to be important to system function, but the extent of spatial organization in the gut ecosystem remains poorly understood. Here, we profile the murine colonic microbiota along longitudinal and lateral axes using laser capture microdissection. We found fine-scale spatial structuring of the microbiota marked by gradients in composition and diversity along the length of the colon. Privation of fiber reduces the diversity of the microbiota and disrupts longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 57 publications
4
67
1
1
Order By: Relevance
“… 17 , 29 Several epidemiological and experimental studies have shown that the health benefits of dietary fibers are related to the composition and function of the intestinal microbiota. 30–32 However, differences in the amount and type of plant derived polysaccharides associated either with short-term or life-long alterations of the microbiota make comparisons difficult. 33–35 For this reason, the current study specifically investigated the effects of cellulose, the most abundant dietary fiber, by feeding normal and gnotobiotic mice fiber-free diets or diets containing cellulose as only fiber source.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 29 Several epidemiological and experimental studies have shown that the health benefits of dietary fibers are related to the composition and function of the intestinal microbiota. 30–32 However, differences in the amount and type of plant derived polysaccharides associated either with short-term or life-long alterations of the microbiota make comparisons difficult. 33–35 For this reason, the current study specifically investigated the effects of cellulose, the most abundant dietary fiber, by feeding normal and gnotobiotic mice fiber-free diets or diets containing cellulose as only fiber source.…”
Section: Discussionmentioning
confidence: 99%
“…The authors revealed that anaerobe classes such as Clostridia, Bacteroidia and Fusobacteria peaked in the summer months and then declined in winter, while, in most cases, facultative anaerobes like LAB showed an inverse trend. Moreover, variations in gut microbial community abundance could be not only affected by seasonal factors but also related to fish physiology and diet 79,80 . In addition, in the present study the reduction of the oxygen level in the environment may have contributed to the modulation of gut microbiota favouring the presence of obligate anaerobic Firmicutes such as Clostridiales.…”
Section: Discussionmentioning
confidence: 99%
“…5a). At the time of BacMix and BacMixC administration, the mouse diet was switched from a standard diet (V1124-300; Ssniff, Soest, Germany) to a isocaloric polysaccharide-deficient chow 76 with sucrose but no cellulose or starch (Ssniff, Soest, Germany). For the BacMixC adoptive transfer, each mouse (n = 10 per group) received 5,000,000 CFU of a 3-bacteria suspension (BacMixC, containing equal numbers of Anaerotruncus sp.…”
Section: Methodsmentioning
confidence: 99%